Glucocorticoid Negative Feedback in Regulation of the Hypothalamic-Pituitary-Adrenal Axis in Rhesus Monkeys With Various Types of Adaptive Behavior: Individual and Age-Related Differences - Goncharova, Nadezhda; Chigarova, Olga; Rudenko, Natalia; Oganyan, Tamara (Frontiers in Endocrinology, 2019)
The study of the mechanisms underlying the increased vulnerability of the individual to stressful environmental factors in different age periods is of great relevance for prevention and effective treatment of stress-dependent diseases that are widespread in the population of aging individuals. The purpose of our study was to investigate the individual and age-related features of the glucocorticoid negative feedback in regulation of the hypothalamic-pituitary-adrenal (HPA) axis, the key adaptive neuroendocrine system, in experiments with physically healthy young and old female rhesus monkeys with administration of mineracorticoid receptor (fludrocortisone) and glucocorticoid receptor (dexamethasone) agonists. We studied the monkeys with increased trait anxiety and depression-like behavior (DAB) characterized, as previously was shown, by the increased vulnerability to acute stress and the animals with normal standard behavior (SB) as the control. The pronounced individual differences in the reaction of HPA axis to fludrocortisone and dexamethasone in young animals were found. Young animals with DAB showed a lower sensitivity of HPA axis to the inhibitory effect of both fludrocortisone and dexamethasone compared with young animals with SB. At the same time, there were no significant intergroup differences in the concentration of ACTH and cortisol in response to placebo injection, i.e. in basal conditions. The old individuals with DAB demonstrated the essential relative resistance of HPA axis to fludrocortisone test and higher basal plasma levels of cortisol and ACTH in the evening (the period of HPA axis low circadian activity) compared to old SB animals. In the same time, the intergroup differences in the response of HPA axis to dexamethasone administration were leveled due to age-related increase in sensitivity of HPA axis to dexamethasone in animals with DAB. These data testify the pronounced intergroup and age differences in the feedback regulation of HPA axis, presumably resulting from unequal individual and age-related changes in the activity of mineralcorticoid and glucocorticoid receptors in the brain structures supporting the functions of HPA axis. The maximum age disorders in functioning of the negative feedback mechanism in the regulation of HPA axis are characteristic of animals with DAB, which, apparently, underlie the increased vulnerability of these animals to stress exposure.